Identification of barriers and enablers to rapid diagnosis along the paediatric stroke chain of recovery using Value-Focused Process Engineering. Issue 1 (2nd January 2021) - Mackay, Mark T.; Churilov, Leonid; Moon, Anna; McKenzie, Ian; Donnan, Geoffrey A.; Monagle, Paul; Li, Qi; Babl, Franz E.
ABSTRACT: Coordinated systems of care are required to improve access to reperfusion therapies in paediatric stroke. A conceptual model was developed to map the process-of-care from symptom onset to confirmation of diagnosis. Value-Focused Process Engineering with event-driven process modelling was used to identify barriers and enablers to timely and accurate paediatric stroke diagnosis. Stakeholder interviews were conducted to inform model design, development, demonstration and validation. Barriers included: (i) ambulance dispatcher failure to allocate high-priority response, (ii) childrens' exclusion from paramedic clinical practice guidelines, (ii) non-allocation of high triage category on hospital arrival, (iii) absence of emergency department guidelines for focal neurological deficits, and (iv) computed tomography as the first imaging investigation. Enablers included: (i) public awareness programs, (ii) childrens' inclusion in prehospital emergency stroke algorithms, (iii) re-organisation of health services, with primary paediatric stroke centres, (iv) implementation of triage and neuroimaging decision support tools, and (iv) rapid stroke MRI imaging protocols.